Wish you were here - Swift, Graham, 1949- (Alfred A. Knopf, 2012)
"A novel set in the Devon countryside in England, in which a man, the son of a dairy farmer, has to cope with the recent death of his brother, a soldier in Iraq; repair his relationship with his wife; and cope with the complicated legacy of his family's past"--